KONSEPSI FIQH PEMERATAAN DAN KEPEDULIAN SOSIAL: PERSPEKTIF AL-QURAN - Uril (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2023)
The problem of social inequality in society turns out to be difficult to solve, even though Islam advocates that wealth does not only revolve around certain circles. This article aims to uncover the factors that gave rise to social inequality during what the prophet Muhammad saw. and the solution. This research approach is qualitative with a type of literature review. Data collection through written works, using the perspective of the Quran and its implementation in the history of the prophet Muhammad. The result of this study is, first, the triggering factor for social inequality during the time of the prophet during the Makkah phase was the boycott of Muslims, resulting in famine. Meanwhile, the triggering factor for social inequality in Medina is the presence of the Muhajirins, which raises several social problems. Second: the solution given to the Makkah case is to open a boycott, and the Medina case with the at-taakhi program, taking away the rights of Muslims from the Quraysh and the program of caring and economic development of the people.